SYARIAH ISLAM DALAM KONTEKS PERGULIRAN SOSIAL, POLITIK, DAN BUDAYA - Sumarna, Elan (Universitas Pendidikan Indonesia, 2016)
Islamic jurisprudence from Al-quran and Al-Hadith which became the only legal nomenclature trial on human life. However, the legislation would still be able to trial on all the problems that would come at any time. In the writing of this paper, the authors use a qualitative approach to the method of study of the literature. Data analysis was done with the analysis of the qualitative data analysis method and content. The results of this study described the process of unification of muslim diversity has always been a paradigm of race and culture. It is crucial even though problems of unification were formed, but political stability will remain difficult to achieve. On the other hand, Muslims are generally always fall on a religious symbols that eventually political conflict difficult halted. In addition, the position of Islamic jurisprudence in muslim countries generally do not appear in the form of blatantly political institution, but rather teralokatif in their culture along with just their understanding of Islam itself.